Pengaruh Mutasi Jabatan dan Penghargaan Terhadap Kinerja Pegawai dengan Motivasi Sebagai Variabel Intervening di PT. Jasa Raharja Surabaya - Indra Widiyawanto; Sri Muljaningsih (UNHI Press, 2023)
In this study, a work motivation variable will be added as an intervening variable in testing the effect of job transfers and awards given to employees, motivation certainly requires employees who have good performance and who work effectively and efficiently. This study aims, to analyze the effect of job transfers directly on the performance of employees at PT. Jasa Raharja Surabaya; to analyze the impact of job transfer through motivation, it affects the performance of employees at PT. Jasa Raharja Surabaya; to analyze the direct effect of rewards on employee performance at PT. Jasa Raharja Surabaya; to analyze the impact of rewards through motivation on employee performance at PT. Jasa Raharja Surabaya. This research is also called research. To get a clear picture and better understand the content, the definitions used in this research can be measured and eliminated and avoid errors in interpretation. This study uses a survey method with a questionnaire as the primary data collector. The population is all employees, totaling 61 employees of PT. Jasa Raharja Surabaya, as for the method using the Proportional Stratified Random Sampling technique, this technique is used because the population is not homogeneous determined by the Taro Yaname formula and the Slovin formula. so that a sample of 6i respondents will be obtained. The data analysis technique used is partial least squares (PLS). The results of the study concluded that; job mutations had a non-significant effect on employee performance; the award has been proven to have a significant positive impact on employee performance; job mutations have a non-significant effect on employee performance through motivation; rewards have a significant positive impact on employee performance through motivation.